PERANAN MAGNESIUM PADA EPILEPSI - I Wayan Widyantara, Anna Marita Gelgel Sinardja (Neurona Majalah Kedokteran Neuro Sains, 2013)
THERAPEUTIC ASPECT OF EPILEPSY IS GROWING FROM THE BEGINNING BY GIVING BROMIDE AS THE FIRSTLINE THERAPY TO THE LATEST GENERATION OF ANTIEPILEPTIC DRUGS THE PRINCIPLE MANAGEMENT OF EPILEPSY IS TO ACHIEVE A HIGH THERAPEUTIC PLASMA CONCENTRATIONS WITH MINIMAL TOXICITY MAGNESIUM IS AN ENDOGENOUS NMDA NMETHYL DASPARTATE RECEPTOR ANTAGONIST THAT IS REQUIRED TO PERFORM ITS NORMAL FUNCTION THE USE OF MAGNESIUM AS ANTICONVULSANTS HAVE LONG BEEN USED PRIMARILY TO PREVENT SEIZURES IN PATIENTS WITH ECLAMPSIA WHICH IS MAINLY USED THE FORM OF MAGNESIUM SULFATE